2020
DOI: 10.1093/cercor/bhaa023
|View full text |Cite
|
Sign up to set email alerts
|

A Domain-General Cognitive Core Defined in Multimodally Parcellated Human Cortex

Abstract: Numerous brain imaging studies identified a domain-general or “multiple-demand” (MD) activation pattern accompanying many tasks and may play a core role in cognitive control. Though this finding is well established, the limited spatial localization provided by traditional imaging methods precluded a consensus regarding the precise anatomy, functional differentiation, and connectivity of the MD system. To address these limitations, we used data from 449 subjects from the Human Connectome Project, with the corte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
323
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 259 publications
(364 citation statements)
references
References 111 publications
39
323
2
Order By: Relevance
“…Second, the set of fronto-parietal regions that we identified here are consistent with prior work, which described a similar canonical cognitive control network (Cole & Schneider, 2007;Dosenbach et al, 2008;Vincent et al, 2008). This network has also been referred to as the multiple-demand network (Camilleri et al, 2018;Duncan, 2010;Duncan & Owen, 2000), in that it exhibits consistent responsivity to increasing control demands across a range of task contexts (Assem et al, 2020;Fedorenko et al, 2013;Shashidhara et al, 2019). This set is primarily bilateral and includes not only mid-lateral prefrontal cortex and parietal cortex, but also other regions linked to cognitive control, such as the anterior insula / frontal operculum, and medial frontal cortex / dorsal anterior cingulate.…”
Section: Initial Dmcc Findingssupporting
confidence: 84%
“…Second, the set of fronto-parietal regions that we identified here are consistent with prior work, which described a similar canonical cognitive control network (Cole & Schneider, 2007;Dosenbach et al, 2008;Vincent et al, 2008). This network has also been referred to as the multiple-demand network (Camilleri et al, 2018;Duncan, 2010;Duncan & Owen, 2000), in that it exhibits consistent responsivity to increasing control demands across a range of task contexts (Assem et al, 2020;Fedorenko et al, 2013;Shashidhara et al, 2019). This set is primarily bilateral and includes not only mid-lateral prefrontal cortex and parietal cortex, but also other regions linked to cognitive control, such as the anterior insula / frontal operculum, and medial frontal cortex / dorsal anterior cingulate.…”
Section: Initial Dmcc Findingssupporting
confidence: 84%
“…The fact that the MD system responds to code problems over and above content-matched sentence problems underscores the role of domain-general executive processes in code comprehension. Although cognitive processes underlying code interpretation bear parallels to logic and math tasks ( Papert, 1972 ; Pennington and Grabowski, 1990 ; Perkins and Simmons, 1988 ) and to natural language comprehension/generation ( Fedorenko et al, 2019 ; Hermans and Aldewereld, 2017 ), the neural activity we observe primarily resembles activity observed in response to domain-general executive tasks ( Assem et al, 2020 ; Duncan, 2010 ; Fedorenko et al, 2013 ). In particular, code comprehension elicits bilateral responses within the MD system, in contrast to math and logic tasks that tend to elicit left-lateralized responses within the MD system, and in contrast to language tasks that elicit responses in the spatially and functionally distinct language system.…”
Section: Discussionmentioning
confidence: 71%
“…We found that responses in the MD system were driven both by the processing of problem content (e.g., summing the contents of an array) and by code comprehension (e.g., identifying variables referring to an array and its elements, interpreting a for loop, realizing that the output of the program is the variable being updated inside the for loop). Both of these processes plausibly require attention, working memory, inhibitory control, planning, and general flexible relational reasoning – cognitive processes long linked to the MD system ( Duncan, 2010 ; Duncan, 2013 ; Duncan and Owen, 2000 ; Miller and Cohen, 2001 ) in both humans ( Assem et al, 2020 ; Shashidhara et al, 2019a ; Woolgar et al, 2018 ) and non-human primates ( Freedman et al, 2001 ; Miller et al, 1996 ; Mitchell et al, 2016 ). A recent study ( Huang et al, 2019 ) reported neural overlap between operations on programming data structures (which require both code comprehension and the processing of problem content) and a mental rotation task (which requires spatial reasoning).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations